Evaluation of enzyme-linked immunosorbent assay (ELISA) and immunofluorescent antibody (IFA) test for the detection of porcine reproductive and respiratory syndrome virus (PRRSV) antibody in pigs from conventional farms - Yahara, Y. (Nisshin Feed Inc., Oi, Saitama (Japan)); Ohkubo, Y; Kariwa, H; Takashima, I (Journal of Veterinary Medical Science, 2002)
To evaluate the immunofluorescent antibody (IFA) test and enzyme-linked immLmosorbent assay (ELISA) for detecting the porcine reproductive and respiratory syndrome virus (PRRSV) antibody, conventional pigs In PRRSV-positive and -negative commercial farms were examined. Antibody development patterns in ELISA and IFA tests were compared in 3 week old piglets experimentally infected with the PRRSV. The virus was detected from 2 days post infection (PI) and then the antibody titers and S/P ratios rose by both methods. A total of 208 serum samples were collected from 4 PRRSV-negative farms and 210 samples from PRRSV-positive farms, and were tested for the PRRSV antibody by IFA and ELISA. The titer of 64 should be set as the cut-off point in IFA for field sera. Similarly, the cut-off S/P ratio should be set at 0.4 in ELISA. A high degree of correlation was observed between antibody titers by the two methods in these 418 samples, with a correlation coefficient of 0.84. The coincidence rate between the two tests was 84.7%(354/418). In non-coincident cases, ELISA was able to detect the antibody with a low titer in the serum samples which were negative in IFA but from PRRSV positive farms. ELISA was more sensitive than IFA to detect PRRSV infected animals or farms.